In silico study: secondary metabolites from malay apple (Syzygium malaccense (L.) Merr. & L.M. Perry) as potential breast cancer treatments - Riska Prasetiawati; Nawadhir Fauzan; Meilia Suherman (Universitas Ahmad Dahlan, 2023)
Breast cancer has the highest prevalence of all cancers. Breast cancer has overtaken lung cancer as the leading cause of global cancer incidence in 2020, accounting for 2,261,419 new cases, or 11.7% of all new cancer cases worldwide. Among the efforts that can be done are efforts to find breast cancer medications that are safe and selective for the treatment and prevention of cancer, particularly those derived from medicinal plants. The Malay apple (Syzygium malaccense (L.) Merr. and L.M. Perry) is one plant that has been extensively examined and proved to have an antiproliferative effect. The pharmacophore modelling, molecular docking, and molecular dynamic approach was conducted on 155 active compounds of Malay apple to alpha and beta estrogen receptors. According on the results of ER-lamda docking, numerous substances have binding free energy values less than 4-OHT yet are not bound to important amino acids, as the result, it is not continued to the next test. On other side, with a fit score of 45.81, rutin was potentially selective for ER-beta receptors, molecular docking to ER-beta obtained that rutin was predicted to have breast cancer activity with a free binding energy value of -10.6 kcal /mol with better conformation and affinity compared to native ligand (genistein), and bound to essential amino acids as anticancer breast at ARG 346, GLU 305, and molecular dynamics simulations show that the compound has good stability when binding to the receptor. In silico toxicity prediction from rutin showed outcomes that match the requirements for the candidate drug. However, because it does not match the ADME prediction and Lipinsky's rule of five, rutin must be optimalization to improve its pharmacokinetic and pharmacological profile before it can be further explored as a therapeutic option for the treatment of breast cancer that targets the ER- receptor.